Riparian Buffers, Connectivity, and Water Quality: A Systematic Review of Land‑Use Gradients in Agro‑Urban Watersheds - Roland Kasim; Fitryane Lihawa; Dewi Wahyuni K. Baderan (Westscience Press, 2025)
Agro‑urban watersheds combine intensive agriculture, expanding settlements, and modified drainage networks that jointly accelerate nutrient, sediment, and thermal pressures on streams. Riparian buffers are widely promoted as nature‑based infrastructure to intercept these pressures, yet reported effectiveness varies because pollutant delivery is mediated by hydrologic and ecological connectivity. This systematic review synthesizes international evidence on how riparian buffer attributes (width, vegetation structure, and integrity) interact with land‑use gradients and connectivity metrics to influence water‑quality indicators (chemical, physical, thermal, and biological). The synthesis shows consistent degradation of water quality with increasing land‑use intensity, but with strong context dependence driven by scale, storm routing, and pathway bypass. Buffers most reliably reduce pollutants when dominant surface and shallow subsurface flowpaths intersect buffer soils; uniform width prescriptions are therefore insufficient without connectivity diagnostics and input‑load context. We further find growing use of graph‑based and hydrologic connectivity measures to prioritize riparian corridors and identify hotspots where restoration can yield the highest water‑quality returns. The review concludes with connectivity‑informed design and planning implications to support water‑quality protection in agro‑urban watersheds.